Well-being of Malaysia's disaster-affected coastal communities - Zahari, Rustam Khairi; Raja Ariffin, Raja Noriza; Asmawi, M. Zainora; Ibrahim, Aisyah Nadrah (Trans Tech Publications Ltd., Switzerland, 2015)
The 26th December 2004 Indian Ocean tsunami unleashed devastation in many countries causing fatalities and massive destruction of properties including a number of coastal communities along the west-coast of Peninsular Malaysia. The objective of this study is to explore the impact of the tsunami to the well-being of the affected coastal communities after a gap of a few years since the 2004 disaster. Close attention was given to the respondents' perceptions with regards to mitigation tools and practices that should be adopted in preparing for any future disasters. Data was collected through questionnaire in tsunami-impacted coastal communities within the area of Kuala Muda in the state of Kedah, Malaysia. It was found that the 2004 tsunami disaster left a significant mark on Malaysia's and the world's disaster management landscape but the tragedy had also scarred the victims in the study area physically, financially and psychologically. The heightened disaster awareness subsequent to the event has further empowered the communities in their involvement in disaster management and steps must be taken to ensure these vulnerable communities are well-equipped to face any eventualities.